Insectalia Technics: Review of Jussi Parikka, Insect Media: An Archaeology of Animals and Technology - Murphy, Graham J. (Humanimalia, 2011)
Jussi Parikka. Insect Media: An Archaeology of Animals and Technology. Posthumanities. Minneapolis: University of Minnesota Press, 2010. 281pp. $25.00